Delayed Diagnosis of Tricuspid Atresia: A Case Report - Ramita Nath Yogi; Som Raj Awasthi; Arun Kumar Mandal; Kiran Shahi; Kamal Prasad Thani; Siddhartha Pradhan (Journal of Nepal Medical Association)
Tricuspid Atresia is a rare cyanotic congenital heart disease that impairs oxygenation. A 16-months female child from a rural area in Nepal presented with shortness of breath, cyanosis of the lips and extremities, feeding difficulties and severe acute malnutrition. Patient had been diagnosed as cyanotic congenital heart disease at nine months but had sought treatment from Shamans due to lack of knowledge along with financial constraints. Diagnostic echocardiography at referred centre had revealed Tricuspid Atresia type IB with a ventricular septal defect. While awaiting surgery, the child collapsed and was revived after cardiopulmonary resuscitation. Emergency surgery was then done. After surgery, the child had a stormy recovery, and was subsequently discharged home, stable. This case emphasizes the need for early diagnosis of cyanotic congenital heart disease through prenatal and postnatal screening and enhancing health education in the community.